Politiques baniwa de la boisson : usages et représentations de l’alcool chez des indiens évangéliques de l’Amazonie brésilienne - Elise Capredon (Centre de Recherches sur les Mondes Américains, 2016)
The scientific literature has already refuted the very widespread – in both North America and Latin America – prejudice that Indians are predisposed to alcoholism. However, very few researchers focused on moderate uses of alcoholic drinks in the contemporaneous native societies. The aim of this paper is to contribute to the deconstruction of the drunken Indian stereotype by exploring, from an ethnological perspective, two types of relations with alcohol not very well documented among native people of Brazil: abstinence and controlled consumption. To this end, we will use ethnographic data collected among the Baniwa, an Arawak-speaking people of Northwest Amazonia. Converted since the mid-twentieth century to Evangelicalism, a Protestant religious movement, the Baniwa renounced to alcohol consumption and turned sobriety into a main marker of their religious affiliation.